2020
DOI: 10.5897/err2019.3848
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emotional literacy, cognitive flexibility and counseling self-efficacy of senior students in psychology and psychological counseling and guidance

Abstract: The aim of this study was to investigate the relationship between emotional literacy, cognitive flexibility and counseling self-efficacy among senior students studying in psychology and psychological counseling and guidance departments. Participants of the study were 397 (306 female and 91 male) undergraduate students enrolled in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In all, the study findings are consistent with previous research which indicated that access to training was positively associated with counselors’ self-efficacy in performing their duties and dealing with educational counseling, such as providing career guidance to students ( Malkoç and Sünbül, 2020 ; Perry et al, 2020 ). The finding is aligned with Perry et al (2020) study whereby counselors who received more training demonstrated a higher level of self-efficacy and better serve students and can assert one’s roles via effective communication in advocating the counselors’ and students’ roles and needs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In all, the study findings are consistent with previous research which indicated that access to training was positively associated with counselors’ self-efficacy in performing their duties and dealing with educational counseling, such as providing career guidance to students ( Malkoç and Sünbül, 2020 ; Perry et al, 2020 ). The finding is aligned with Perry et al (2020) study whereby counselors who received more training demonstrated a higher level of self-efficacy and better serve students and can assert one’s roles via effective communication in advocating the counselors’ and students’ roles and needs.…”
Section: Discussionsupporting
confidence: 91%
“…A study of 180 Greek school career counselors found counselors showed higher confidence, felt empowered after having adequate training access and opportunities, and as a result, it increased their professional efficacy and competencies (Kounenou et al, 2010(Kounenou et al, , 2018. Additionally, programs such as counseling preparation programs or continuous professional training attended by counselors, too, increased their self-efficacy (Malkoç and Sünbül, 2020;Perry et al, 2020). Thus, we hypothesized: Hypothesis H 5 : There is a significant positive relationship between access to training and counseling self-efficacy among school counselors.…”
Section: Access To Training Perceived Supervisor Support Of Training and Counseling Self-efficacymentioning
confidence: 99%
“…According to Ashe et al, (2021) is one manifestation of a systematic activity on how to plan a guidance and counseling activity, mobilize human resources in the guidance and counseling organization to achieve goals, and supervise how guidance and counseling activities are carried out, all of which are related to the concept of administration. Guidance and counseling efforts are evaluated and counseled continuously (Asude & Zeynep, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding empirical results, in their review, Larson and Daniels (1998) reported associations of higher CSE ratings with greater positive and less negative (especially anxiety) affect with respect to the therapeutic role. Negative relations to physiological stress ( Lannin et al, 2019 ) and positive relations with cognitive flexibility and emotional literacy ( Asude and Zeynep, 2020 ) were also discussed. Additionally, several studies indicated positive relations of CSE with therapeutic and supervisory experience (e.g., Larson et al, 1992 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%